ANALISIS PEMBENTUKAN UNI MONETER ASEAN-5 DENGAN PENDEKATAN PARITAS INTERNASIONAL DALAM HUBUNGAN KESEIMBANGAN NILAI TUKAR JANGKA PANJANG (1980.01 â 2004.12) - Rahayu, Siti Aisyah Tri; Hakim, Lukman (Universitas Muhammdaiyah Surakarta, 2007)
In order to strengthening cooperation regional and form the strength regional in ASEAN, likely require to relate at successful European Union in forming financial and economic market integration (EMU). ME become the âmodel